Small ruminant value chain and empowerment: a gendered baseline study from Ethiopia - Kinati, Wole; Temple, Elizabeth C.; Baker, A. Derek; Najjar, Dina (Frontiers Media, 2023)
Introduction: Despite growing interest in gender analysis in value chains, comparatively few studies have analyzed gender relations in small ruminant value chains using sex-disaggregated quantitative data in livestock-based systems.